Evaluation of IPv4 and IPv6 in Testbed Performance - Daw, Daw Abdulsalam Ali (2009)
The urgent need for IP addresses, which led to drive for IPv6 implementation, which is considered the only alternative to meet the needs of new users. There is no doubt that the change from IPv4 to IPv6 is not uncomplicated, whereas the users already feel at ease about using IPv4. Our main goal in this project is to design an experimental network testbed for the next generation network research in order to use this network in evaluating the performance of IPv4 and IPv6 towards other applications. This report explains and documents the process of implementing an IPv6 testbed using based machines running Linux Redhat. The steps taken to verify the functionality of the testbed have also been documented.